Elevated thermoelectric figure of merit of n-type amorphous silicon by efficient electrical doping process. (February 2018) - Banerjee, Debashree; Vallin, Örjan; Samani, Kabir Majid; Majee, Subimal; Zhang, Shi-Li; Liu, Johan; Zhang, Zhi-Bin
Abstract: The currently dominant thermoelectric (TE) materials used in low to medium temperature range contain Tellurium that is rare and mild-toxic. Silicon is earth abundant and environment friendly, but it is characterized by a poor TE efficiency with a low figure of merit, ZT . In this work, we report that ZT of amorphous silicon (a-Si) thin films can be enhanced by 7 orders of magnitude, reaching ∼0.64 ± 0.13 at room temperature, by means of arsenic ion implantation followed by low-temperature dopant activation. The dopant introduction employed represents a highly controllable doping technique used in standard silicon technology. It is found that the significant enhancement of ZT achieved is primarily due to a significant improvement of electrical conductivity by doping without crystallization so as to maintain the thermal conductivity and Seebeck coefficient at the level determined by the amorphous state of the silicon films. Our results open up a new route towards enabling a-Si as a prominent TE material for cost-efficient and environment-friendly TE applications at room temperature. Graphical abstract: Highlights: The thermoelectric figure of merit, ZT, of amorphous Si films has been increased to ∼0.64 at room temperature. The efficient doping by arsenic implantation and low temperature annealing led to increase of the electrical conductivity, σ. The enhancement of ZT is realized by increasing σ rather than by decreasing κ as often used in the nano-structuring strategy. By annealing at temperatures close to that of growth, the Si film shows σ akin to crystallized films while still amorphous.